The influence of concentration, endurance and confidence on the shooting ability of PERBAKIN athletes - Fadilla, Nailatul; Irawan, Roma; Komaini, Anton; Rasyid, Willadi (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: The problem of this research is the low shooting ability of pistol athletes. Low shooting ability is influenced by several factors, such as concentration, endurance and self-confidence. Purpose: This study aims to reveal the direct and indirect effects, as well as the simultaneous influence between variables. Methods: This type of research is quantitative associative with a path analysis approach. Results: The results of hypothesis testing show: (1) there is a direct effect of concentration on shooting ability (py1 = 0.334 or 11.1%), (2) there is a direct effect of endurance on shooting ability (py2 = 0.349 or 12.1%), (3 ) there is a direct effect of self-confidence on shooting ability (py3 = 0.440 or 19.3%), (4) there is an indirect effect of concentration on shooting ability through self-confidence (p31.py3 = 0.234 total effect 32.3%), (5 ) there is an indirect effect of endurance on shooting ability through self-confidence (p32.py3 = 0.272 total effect 38.6%), and (6) there is an effect of flexibility, agility and concentration simultaneously on shooting ability (Rsquare = 0.931 or 93 ,1%). Conclusion: The Ability of Table Tennis Footwork of Extracurricular Students of SMP N 2 Tungkal Ulu is influenced by the three factors that have been explained or it can be interpreted, that the ability of Table Tennis Footwork can be improved if athletes have good flexibility, agility and concentration variables. The efforts that can be made are increasing flexibility, agility and concentration by doing exercises in a planned, continuous manner and in accordance with the principles of training.